"Garden walk – on the road to health", a new informative and health-improving route at the Petrozavodsk State University Botanical Garden - Platonova Elena; Eglacheva Arina; Obuhova Elena; Falin Alexey (Hortus Botanicus, 2015)
The article describes the new informative and health-improving route, "A garden walk - on the road to health", of the Petrozavodsk State University Botanical Garden. The route has been developed for the older generation; however, in the future, citizens and guests of the city of different age groups will be able to take this route. The path goes through the most beautiful and interesting exhibitions, collections and natural areas of the garden; information about health-improving qualities of local and introduced plants and the northern nature is provided along the way. Results of the year 2015 proved the importance of this project, as well as the need to create more therapeutic parks and gardens. The article presents outcome of the project "The Open Garden" at the municipal public institution "Integrated Social Service Center of Pryazha region - Nadezhda" in the village of Essoila (Karelia).